2010
DOI: 10.1002/mus.21808
|View full text |Cite
|
Sign up to set email alerts
|

The 6‐minute walk test in Duchenne/Becker muscular dystrophy: Longitudinal observations

Abstract: In this study we used the 6-minute walk distance (6MWD) to characterize ambulation over time in Duchenne/Becker muscular dystrophy (DBMD). The 6MWD was assessed in 18 boys with DBMD and 22 healthy boys, ages 4-12 years, over mean [range] intervals of 58 [39-87] and 69 [52-113] weeks, respectively. Height and weight increased similarly in both groups. At 52 weeks, 6MWD decreased in 12 of 18 (67%) DBMD subjects (overall mean [range]: 357 [125-481] to 300 [0-510] meters; Δ -57 meters, -15.9%), but increased in 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
168
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(184 citation statements)
references
References 32 publications
10
168
0
6
Order By: Relevance
“…The 6MWT was performed by specifically trained physiotherapists according to accepted clinical standards 19. Assessments were done annually for the Italian DMD Registry, and at routine clinical visits in the LNMRC study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 6MWT was performed by specifically trained physiotherapists according to accepted clinical standards 19. Assessments were done annually for the Italian DMD Registry, and at routine clinical visits in the LNMRC study.…”
Section: Methodsmentioning
confidence: 99%
“…The 6MWT is an ambulatory outcome measure that has been utilized in clinical trials for 3 DMD therapeutics (eteplirsen, drisapersen, and ataluren) and has been shown to be accurate and reproducible 13. Understanding of DMD disease progression as measured by 6MWT has increased in recent years with publications of natural history data14, 15, 16, 17, 18, 19 as well as placebo‐arm reporting from DMD trials 20, 21, 22. Published data support that on average, 6MWT distance is stable or increases in patients <7 years of age, whereas it declines in older patients 15, 17, 18, 23, 24.…”
mentioning
confidence: 99%
“…However, 6MWT distance did not show a significant difference in cross-sectional comparisons between corticosteroidtreated and corticosteroid-naive boys. Although the 6MWT has been established as a clinically meaningful outcome measure in DMD, 31 it is less sensitive in monitoring muscle response to disease progression in younger boys (,7 years old). 31,32 The reduced sensitivity of the 6MWT in younger boys with DMD has been attributed to the fact that disease-related progressive loss of muscle strength and function might be overshadowed by normal growth and development.…”
Section: Impact Of Initiation Of Corticosteroid Therapy In Boysmentioning
confidence: 99%
“…Os pacientes com DMD possuem algumas características como disfunção miocárdica e/ou redução de massa muscular esquelética funcional 21 , além da ausência da proteína distrofina que é crítica para a estabilidade estrutural do esqueleto, do diafragma, e dos músculos do coração 22 . Em um estudo recente com utilização do teste TC6 em pacientes com DMD no solo, foi verificado um maior gasto energético durante esse teste, nesses indivídu-os 23 .…”
Section: Discussionunclassified